DYNAMICS OF OVERSIGHT OF PUBLIC POLICY FROM THE PERSPECTIVE OF STATE ADMINISTRATIVE LAW IN THE DIGITAL ERA - Manurung, Ardana Maharani; Simanjuntak, Stefani Losanti; Karo-Karo, Selvia Br (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
The digital revolution has transformed the delivery of public services in Indonesia through digitalization processes and electronic-based government systems (SPBE). This change makes it easier for the public to access services, reduces corruption practices, and enhances government transparency and accountability. Nevertheless, there are several legal challenges in managing digital services, such as questions about the validity of digital administrative decisions, liability for system errors, differences in digital access, and personal data protection. This study uses a normative legal approach by analyzing legislation and related literature. The research findings indicate that administrative law plays an important role in overseeing and improving the performance of effective, efficient, transparent, and accountable governance, while also serving as the legal foundation for inclusive and equitable digital transformation. Problems in implementing digitalization Public services such as infrastructure disparities, digital literacy gaps, bureaucratic unwillingness to change, data security issues, and incomplete policies need to be addressed with a flexible and integrated legal approach.